FENOMENA KORUPSI PEJABAT PUBLIK DI JAWA BARAT DAN CARA MENGATASINYA - Atnan, Nur (Faculty of Law, Parahyangan Chatolic University, 2015)
Abstract The negative effect of the decentralization policy implemented since 2001 is that corruption too become decentralized, especially in West Java. This article discusses: (1) patterns of corruption; (2)probable causes of corruption by government officials; and (3) proposed solution. To do just that, the author chose a socio legal research approach. Empirical data was collected through in depth interview.Â The main findings are: (1) Corruption in West Java mostly took the form of state budget misappropriation; (2) the major source of corruption is abuse of power, money politics and the tendency to misuse loopholes in rules and regulations.Â Law enforcement should therefore focus on betterment of regulation, organizational structure and legal culture of the officers.